Impact of postoperative pulmonary hypertension on outcome after heart transplantation. (4th May 2017) - Lundgren, Jakob; Söderlund, Carl; Rådegran, Göran
Abstract: Objectives: We wanted to investigate the effects of postoperative pulmonary hypertension (PHpostop : mean pulmonary artery pressure [MPAP] ≥ 25 mmHg), diastolic pressure gradient (DPG), pulmonary vascular resistance (PVR), and repeated hemodynamic measurements on long-term survival after heart transplantation (HT). Design: Eighty-nine patients who underwent HT at Skåne University Hospital in Lund in the period 1988–2010 and who were evaluated with right-heart-catheterization at rest, prior to HT and repeatedly during the first postoperative year, were grouped based on their MPAP, DPG, and PVR. Results: One year after HT, survival was lower in patients with PHpostop than in those without, in patients with DPG ≥7 mmHg than in those with DPG <7 mmHg, and in patients with PVR >3 WU than in those with PVR ≤3 WU. Moreover, compared to patients with no PHpostop or with PHpostop at one evaluation during the first year after HT, PHpostop at repeated evaluations was associated with higher mortality (hazard ratio 3.4, 95% CI 1.4–8.0). There was no significant difference in acute cellular rejection between patients with and without PHpostop, but postoperative kidney function was worse in patients with repeated PHpostop . Conclusions: When defined according to present guidelines, PH one year after HT may emerge as a prognostic marker for long-term outcome after HT. Moreover, PHpostop at repeated evaluations during the first year after HT had stronger prognostic value than PHpostop at a single examination, illustrating a means of identifying a high-risk population. However, confirmation in larger multi-center studies is warranted.